The Dynamics of Interaction and the Meaning of Presence in a Digital Work Environment: Efforts to Maintain Human Values in the Modern Workplace - Thalita Putri Jaelani; Hana Fauziah Rahayu (Asosiasi Ahli Administrasi Indonesia, 2026)
Digital transformation has fundamentally changed modern office management practices, particularly in how people work, communicate, and build social relationships within organizations. The shift from physical to virtual presence mediated by technology has improved efficiency, flexibility, and productivity. However, this transformation also presents challenges to essential human values such as empathy, solidarity, fairness, and emotional balance among employees. This study aims to examine the dynamics of interaction and the meaning of presence within the context of digital office management while formulating conceptual strategies to sustain human values amid the ongoing paradigm shift. Using a qualitative method through a literature review approach, this research highlights the concept of presence management as a strategic framework that places humans at the core of digital work systems. The findings emphasize the need to balance technological advancement with employees’ psychological well-being through the implementation of policies such as the right to disconnect, flexible working hours, and empathetic digital communication guided by ethical principles. The human-centered office management approach is crucial for fostering productive, inclusive, and sustainable digital workplaces, while ensuring that technological advancements do not diminish the value of human presence or erode the core values of humanity in modern office management.